2013
DOI: 10.1016/j.jnutbio.2012.04.010
|View full text |Cite
|
Sign up to set email alerts
|

DHA-fluorescent probe is sensitive to membrane order and reveals molecular adaptation of DHA in ordered lipid microdomains

Abstract: Docosahexaenoic acid (DHA) disrupts the size and order of plasma membrane lipid microdomains in vitro and in vivo. However, it is unknown how the highly disordered structure of DHA mechanistically adapts to increase the order of tightly packed lipid microdomains. Therefore, we studied a novel DHA-Bodipy fluorescent probe to address this issue. We first determined if the DHA-Bodipy probe localized to the plasma membrane of primary B and immortal EL4 cells. Image analysis revealed that DHA-Bodipy localized into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…The discrepancy between our fi ndings and the two aforementioned studies may be due to differences between the composition and the levels of the fat source ( 43,44 ). This study relied on a moderate dose of milkfat (45% of total kilocalories), modeling human suggest that when these fatty acids interact with ordered domains, they increase their molecular order and can adapt to the ordered environment ( 58,59 ). This may be driven by several variables, which include the loss of AA, a highly disordered fatty acid, and a displacement of cholesterol between disordered and ordered domains ( 58,60 ).…”
Section: Implications For the General Public And Clinical Trialsmentioning
confidence: 59%
“…The discrepancy between our fi ndings and the two aforementioned studies may be due to differences between the composition and the levels of the fat source ( 43,44 ). This study relied on a moderate dose of milkfat (45% of total kilocalories), modeling human suggest that when these fatty acids interact with ordered domains, they increase their molecular order and can adapt to the ordered environment ( 58,59 ). This may be driven by several variables, which include the loss of AA, a highly disordered fatty acid, and a displacement of cholesterol between disordered and ordered domains ( 58,60 ).…”
Section: Implications For the General Public And Clinical Trialsmentioning
confidence: 59%
“…These differences have been attributed to the saturated nature of sphingolipid acyl chains that packs well with the rigid cholesterol backbone and separate from DHA containing phospholipids. DHA chains are disordered and enhance the segregation of cholesterol into SM-rich/sterolrich rafts, favoring DHA-rich domains via cholesterol exclusion but DHA chains can also partition into rafts [55].…”
Section: Tablementioning
confidence: 99%
“…Teague et al reported that a DHA-fluorescent probe was highly uptaken by EL4 cells at 37°C than at 23°C, which could be attributed to the high fluidity of the cell membrane at 37°C, while it is more ordered at 23°C [28]. Robinson et al found that DHA was initially incorporated into phosphatidylethanolamine (PE) accompanied by a less amounts into phosphatidylcholine (PC) or other phospholipid classes [29-30].…”
Section: Introductionmentioning
confidence: 99%